Interaction of drugs with lipid raft membrane domains as a possible target - Hironori Tsuchiya; Maki Mizogami (AboutScience Srl, 2020)
Introduction: Plasma membranes are not the homogeneous bilayers of uniformly distributed lipids but the lipid complex with laterally separated lipid raft membrane domains, which provide receptor, ion channel and enzyme proteins with a platform. The aim of this article is to review the mechanistic interaction of drugs with membrane lipid rafts and address the question whether drugs induce physicochemical changes in raft-constituting and raft-surrounding membranes. Methods: Literature searches of PubMed/MEDLINE and Google Scholar databases from 2000 to 2020 were conducted to include articles published in English in internationally recognized journals. Collected articles were independently reviewed by title, abstract and text for relevance. Results: The literature search indicated that pharmacologically diverse drugs interact with raft model membranes and cellular membrane lipid rafts. They could physicochemically modify functional protein-localizing membrane lipid rafts and the membranes surrounding such domains, affecting the raft organizational integrity with the resultant exhibition of pharmacological activity. Raft-acting drugs were characterized as ones to decrease membrane fluidity, induce liquid-ordered phase or order plasma membranes, leading to lipid raft formation; and ones to increase membrane fluidity, induce liquid-disordered phase or reduce phase transition temperature, leading to lipid raft disruption. Conclusion: Targeting lipid raft membrane domains would open a new way for drug design and development. Since angiotensin-converting enzyme 2 receptors which are a cell-specific target of and responsible for the cellular entry of novel coronavirus are localized in lipid rafts, agents that specifically disrupt the relevant rafts may be a drug against coronavirus disease 2019.